Perceptions and attitudes toward elder abuse: cross-sectional study in Hodeidah, Yemen - Bushra Amer; Monia T. Alhadad; Roselit Mathew; Nadir Abdelrahman; Mamun A.N. Qasem (Journal of the Arab Society for Medical Research)
Background/aim Elder abuse and neglect remain significant yet underrecognized issues worldwide, particularly in low-resource settings like Yemen. This study aims to assess societal attitudes toward elder mistreatment in Hodeidah, Yemen, focusing on knowledge, perceptions, and the perceived responsibility of community members in reporting and addressing such incidents. Patients and methods A cross-sectional study was conducted with 314 participants of both sexes living in Hodeidah, Yemen. The majority of participants were female (70.4%), with ages ranging from 18 to 65 years. An online questionnaire was used to evaluate awareness, attitudes, and perceived responsibility regarding elder abuse. This study examined factors, such as sex, family size, marital status, and education level in relation to perceptions of elder mistreatment. Results Findings revealed a high awareness of physical, emotional, and financial abuse, as well as caregiver neglect, with 97.3% of participants recognizing elder abuse as a criminal offense. However, only 75.5% felt personally responsible for reporting cases of mistreatment. Most respondents rejected blaming older adults for abuse, instead attributing household conflicts to external factors. While 98.1% viewed preventing elder abuse as a personal duty, 97.1% considered placing elderly individuals in nursing homes a form of neglect, reflecting strong cultural values favoring family-based care. These findings underscore the need for targeted education, improved intergenerational communication, and policies to strengthen elder protection in Yemen Conclusion This study provides a systematic exploration of public perceptions of elder abuse and neglect in Yemen, focusing on the Hodeidah Governorate. The findings reveal a strong awareness of various forms of mistreatment, including physical, emotional, and financial abuse and caregiver neglect.